Development of Educational Comics Based on A Restorative Approach to Handle Bullying Behavior in Elementary Schools - Sakura Alwina (Institut Agama Islam Negeri Palopo, 2025)
The type of research is research and development. This type of research uses the Four-D model has the stages of Define, Design, Develop, and Disseminate. This research was conducted at SD IT Izzatul Islam. The study was conducted in April to June the academic year 2024/2025. The subjects in this study were grade IV students, totaling 28 people, consisting of 16 male students and 12 female students. The object in this study is an educational comic based on a restorative approach. Data collection techniques are observation, questionnaire, and test. Data analysis used quantitative and qualitative. This research uses a Likert scale that is 1 not good, 2 quite, 3 good, 4 very good. Based on the results of the feasibility test conducted by media experts and material experts, it can be seen that the results of validation carried out by media experts with a percentage of 94.80% are included in the very feasible category, and the validation results of material experts with a percentage of 89.95% include a very decent category. Based on the pretest and posttest tests that have been carried out, it can be concluded that educational comics based on restorative approaches that are developed effectively in increasing the awareness and ability of elementary school students in dealing with bullying behavior are more empathized, reflective, and responsible. Based on the description above, it can be concluded that educational comics are based on a decent and effective restorative approach to SD ITI Izzatul Islam.